Little Monkey lost - Du Quette, Keith (New York : G. P. Putnam's Sons, 2007)
Bored, Little Monkey sets out to find adventure in the jungle and meets nine different kinds of monkeys who teach him fun new things, but not how to get home. Includes facts about the New World Monkeys featured.
Accelerated Reader AR
Keywords: Monkeys -- Juvenile fiction; Jungles -- Juvenile fiction; Missing children -- Juvenile fiction